Real-World Outcomes of Patients With Non-Valvular Atrial Fibrillation on Anticoagulants Ineligible for Phase III Trials of Direct Oral Anticoagulants ― A Retrospective Cohort Study - Higa, Mayumi; Morimoto, Takeshi; Ikeda, Masayuki; Ueda, Shinichiro (Circulation Reports, 2025)
Background: Many patients with non-valvular atrial fibrillation (NVAF) on direct oral anticoagulants (DOACs) in real-world practice were ineligible for DOAC phase III trials. We aimed to determine the proportion of Japanese patients with NVAF eligible for these trials and compare the characteristics and outcomes of ineligible and eligible patients to determine the generalizability of the trial results.Methods and Results: This retrospective cohort study included 7,826 Japanese NVAF patients on warfarin from 71 hospitals. We assessed trial eligibility and analyzed outcomes (major bleeding, stroke/systemic embolism, all-cause mortality) using Cox proportional hazards models. Nearly half (48.2%; n=3,772) of the patients were ineligible for DOAC phase III trials. Ineligible patients were older with more comorbidities and exhibited significantly higher risks of death (unadjusted hazard ratio [HR] 2.84; 95% confidence interval [CI] 2.36–3.43; P<0.0001), stroke/systemic embolism (unadjusted HR 1.53; 95% CI 1.17–1.98; P=0.0016), and major bleeding (unadjusted HR 2.00; 95% CI 1.63–2.44; P<0.0001) compared with eligible patients.Conclusions: Half of the NVAF patients receiving anticoagulant therapy in real-world practice were ineligible for phase III DOAC trials, primarily due to safety concerns. This population differs substantially from eligible patients in characteristics and outcomes. The generalizability of phase III results to real-world patients remains uncertain, warranting additional assessment.